Immunogenicity of specific Bordetella pertussis surface antigens in diphtheria-tetanus-pertussis (DTP) vaccines. - Blaskett, A. C. (Cambridge University Press, 1988)
The predominant causative organism of whooping cough in Australia is of a serotype which has normally been associated overseas with unvaccinated communities. Australian DTP vaccines pass the statutory mouse test for Bordetella pertussis potency but this test is now believed to be relatively insensitive to certain factors, especially the major type-specific agglutinogens, which are presumably also important in the human host-parasite relationship. Because endemic B. bronchiseptica infections make some laboratory animals unsatisfactory for testing B. pertussis agglutinin responses, we have developed a test in which young farm sheep were immunized with vaccines. Type-specific agglutinins in their sera were assayed after absorption of non-specific agglutinins by suspensions of selected bordetella strains. Three well-reputed European DTP vaccines and two recent batches of Australian DTP vaccine were tested and compared thus. All evoked significant agglutinin responses to the main agglutinogens.